Efisiensi Perangkat Pendukung dalam Pelaksanaan Sistem Informasi e-Puskesmas Kota Sungai Penuh - Fitri Dona; Susmiati Susmiati; Dewi Murni (Universitas Batanghari Jambi, 2019)
The implementation of e-Puskesmas can produce accurate and standardized report data so that health services can be effective and efficient so that the incidence of disease outbreaks in the community can be immediately addressed and addressed by health workers at the Sungai Penuh City Health Care. To analyze the description of supporting devices efficiency in the implementation of the e-Puskesmas information system. Descriptive quantitative, a sample of 55 units supporting the implementation of e-Puskesmas was taken using total sampling. The average hardware score of good e-Puskesmas was 74.5% and the average hardware score of e-Puskesmas was 25.5%. The average score of good e-Puskesmas software was 36.4% and the average score of e-Puskesmas software was not good at 63.6%. The average score of the complete e-Puskesmas data is 45.5% and the average score of incomplete e-Puskesmas data is 54.5%. The average score of the good e-Puskesmas network was 27.3% and the average score of the e-Puskesmas network was not good at 72.7%. It was found that the supporting devices for the implementation of e-Puskesmas had not been optimally updated at Sungai Penuh city health care. Evaluate and supervise the supporting devices for implementing the e-Puskesmas information system so that health services are effective and efficient.